Naujųjų technologijų poveikis tarptautinei komunikacijai: viešosios diplomatijos atvejis - Ociepka, Beata (Information & Media, 2012)
The Impact of New Technologies on International Communication: The Case of Public DiplomacyBeata OciepkaThe events in North Africa in the spring of 2011 again attracted the attention of the world public opinion to social media because of their use by opposition for initiatinga social change. The paper raises the question whether social media might play any role in international communication. To answer the question, the case of public diplomacy as a form of political international communication of Central and Eastern European newcomers to the European Union is analyzed. Social media are seen as tools supporting the old networks built thanks to classical tools of diplomacy and contributing to the development of new digital networks. However, the analysis of using of social media by ministries and ministers of foreign affairs as hubs or knots of networks in public diplomacy does not convince as to their any contribution to the development of the relational model of public diplomacy in the region. More optimism might be derived from the online presence of the Belsat television, a channel broadcasting in Belarusian from Poland to Belarus in order to achieve social changes though international broadcasting and social media.Key words: social media, public diplomacy, international communication, new media